Effects of Light Intensity and Daylength on Growth and Flowering of Siam Tulip (Curcuma Alismatifolia Var Chiangmai Pink) - Chin, Flora Lee Sa (2007)
Three studies were conducted to produce high quality potted and cut flowers of Curcuma alismatifolia var Chiangmai Pink, to develop a production protocol for the future use of commercial field growers and to introduce this species as a new ornamental crop to further enhance the lucrative floriculture industry in Malaysia. The morphological changes during flowering were characterized using scanning electron microscopy. In addition, influences of light intensity and daylength on flowering of Curcuma alismatifolia var Chiangmai Pink were investigated in two separate experiments. The objectives of the first study were to study the morphology, inflorescence initiation and flower development of C. alismatifolia using scanning electron microscopy and also to develop a time line of flowering of the crop. The observation from this study showed that the inflorescence was a mixed inflorescence called the thyrse, the main axis was indeterminate and secondary axis was determinate. Apex of the main axis produced primary bracts continuously. The flowers consisted of a gamosepalous calyx, three petals, a polliniferous stamen, a labellum developed from two petaloid staminodes, two lateral petaloid staminodes and a pistil. Ovary and ovules developed in a trilocular style with axial placentation. Initiation and development of the inflorescences can be best described with the number of leaves on the plant. The vegetative stage occurred at 1-4 leaves stage where as the flowering stage was at 5-6 leaves stage. For study two, the objective was to determine the effects of shading on the growth and flower development of Curcuma alismatifolia. Four levels of shading consisting of T1 (0% shade, without using black net), T2 (30% shade), T3 (50% shade) and T4 (70% shade) were used. The average light intensity measured was T1 (1108 mol m-2s-1), T2 (645.32 mol m-2s-1), T3 (402.08 mol m-2s-1) and T4 (296.86 mol m-2s-1). Increasing shade levels increased plant height and flower stalk length of C. alismatifolia. Manipulation of shade levels in cultivation of this species is especially important where 30% shade seemed to be the most suitable for pot flower production. For cut flower production, 70% shade are more suitable with 82.70 cm tall plants and produced flower stalk of 78 cm. In terms of flower quality, plants of 30% shade were the best in the aspect of flower colour, size and more turgid peduncle. Postproduction productivity was also the longest at 43 days. Hence, production of potted and cut flowers of Curcuma alismatifolia using shade level of 30% for the former and 70% for the latter would hasten plants production for commercial purposes The objective of the last study was to study the effect of daylength on the performance of Curcuma alismatifolia in Malaysia. Rhizomes of C. alismatifolia var Chiangmai Pink were grown under five treatments of long days at 12 hour (control), 14 hour, 16 hour, 18 hour and 20 hour. Treatments were supplemental lighting with incandescent bulb of 0 hr, 2 hr, 4 hr, 6 hr and 8 hr after 1900 hr. The study showed that 16 hr photoperiod produced the best growth rate. Plants at 16 hour also gave the best quality flowers with suitable plant height as potted plants, uniform flowering and also intense flower colour. Inflorescence length of Curcuma alismatifolia under this treatment also was the best size with 11.85 cm. Inflorescences of control were too short with less true flowers and shorter bracts where as inflorescences of plants under 20 hour were too long and thin with smaller true flowers. Post production of Curcuma alismatifolia under 16 hour were at 43 days. Introduction of this species as a new flowering potted and cut flower in Malaysia will be very promising as Curcuma alismatifolia is easy to grow with manipulation of shade levels and daylength. This plant species also require less maintenance as it has few pest and diseases problems. Future study on the vase life of the cut flower of Curcuma alismatifolia var Chiangmai Pink, the study on the dormancy, post harvest technology and storage condition for the rhizome of Curcuma alismatifolia should also be conducted to further enhance the growth and flowering of this species for commercial production.